ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MERGER DAN AKUISISI - Prisya Esterlina; Nila Nuzula Firdausi (Jurnal Administrasi Bisnis, 2017)
The research aimed to examine the conditions of companies' financial performance before and after conducting merger and acquisition. Indonesia Stock Exchange (IDX known as BEI) noticed that a whole sector in thirty companies did a merger and acquisition during 2010-2012 periods, except financial sector.Using financial ratio as the parameter of financial performance, it turned out to be the variables that used in this research were current ratio, total asset turnover, fixed asset turnover, debt to equity ratio, debt to asset ratio, net profit margin, return on equity, return on asset,earnings per share. This research used descriptive quantitative and the data was collected fromwww.idx.co.id. Paired sample t-test, wilcoxon sign rank test and manova test were used as the hypothesis test. There are two results which occurred in this research, the first is using manova test at once toward whole financial ratios and there is no significant difference in entire comparison periods. The second result of a partial test which was using paired sampel t-test and wilcoxon sign rank testis obtained by the difference of some significant financial ratios such as current ratio, total asset turnover, fixed asset turnover, debt to equity ratio, net profit margin, return on asset, earnings per share over several comparison periods. Keyword : Financial Ratios, Financial Peformance, Mergers And Aquisition ABSTRAK Tujuan penelitian ini untuk mengetahui keadaan kinerja keuangan perusahaan sebelum dan sesudah melakukan merger dan akuisisi. Terdapat 30 perusahaan yang tercatat di Bursa Efek Indonesia,  kecuali sektor keuangan yang melakukan kegiatan merger dan akuisisi pada periode 2010-2012.  Kinerja keuangan perusahaan diukur melalui rasio keuangan dengan menggunakan variabelcurrent ratio, total asset turnover,  fixed asset turnover, debt to equity ratio, debt to asset ratio, net profit margin, return on equity, return on asset, earnings per share. Jenis penelitian yang digunakan yaitu deskriptif kuantitatif, dan pengambilan data berasal dari www. idx.co.id. Uji hipotesis yang digunakan yaitu uji Paired Sampel T-Test, wilcoxon sign rank test, dan Manova. Ada dua hasil yang di dapatkan dari penelitian ini, yang pertama menggunakan uji manova untuk menguji seretak semua rasio keuangan, dan hasilnya tidak ditemukan perbedaan yang signifikan pada seluruh periode perbandingan. Kedua,hasil dari uji parsial dengan menggunakan paired sampel t-test dan wilcoxon sign rank test didapatkan adanya perbedaaan yang signifikan pada beberapa rasio keuangan seperti current ratio, total asset turnover,  fixed asset turnover, debt to equity ratio, net profit margin, return on asset,  earnings per share pada beberapa periode perbandingan. Kata Kunci : Rasio Keuangan, Kinerja Keuangan, Merger Dan Akuisisi